On ‘Creative Cities’ governance models: a comparative approach - Costa, P. (2007)
The implementation of ‘Creative Cities’ projects, all over the world, in recent years, has been characterized by a great diversity of institutional frameworks and governance mechanisms. Departing from the contemporary debates on “creative industries” and “creative cities”, this paper aims to discuss this diversity of regulatory mechanisms and governance forms. Some tentative typologies of case studies and governance mechanisms are drawn in order to improve the understanding of those dynamics, to build up knowledge on suitable ‘Creative Cities’ governance models, and to develop ideas to support a strategy for public intervention in the Portuguese case.